Some Properties of Certain New Subclasses of Analytic Functions: Some Properties of Certain New Subclasses of Analytic Functions - El-Ashwah, Rabha M.; Hassan, Alaa H. (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
In this paper, we introduce some new subclasses of analytic functions related to starlike, convex, close-to-convex and quasi-convex functions defined by using a generalized operator. Inclusion relationships for these subclasses are established. Also, we introduce some integral-preserving properties. Moreover, connections of the results presented here with those obtained in earlier works are pointed out.